2023
DOI: 10.3847/2041-8213/acc84b
|View full text |Cite
|
Sign up to set email alerts
|

Synchrotron Radiation Dominates the Extremely Bright GRB 221009A

Abstract: The brightest gamma-ray burst, GRB 221009A, has spurred numerous theoretical investigations, with particular attention paid to the origins of ultrahigh-energy TeV photons during the prompt phase. However, analyzing the mechanism of radiation of photons in the ∼MeV range has been difficult because the high flux causes pileup and saturation effects in most GRB detectors. In this Letter, we present systematic modeling of the time-resolved spectra of the GRB using unsaturated data obtained from the Fermi Gamma-ray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 51 publications
(47 reference statements)
4
18
1
Order By: Relevance
“…In the energy spectrum analysis, we found that there may be a photosphere emission component in the early phase of GRB 230307A, which is similar to that of the also very bright GRB 130427A (Preece et al 2014). However, the brightest of all time (the BOAT, GRB 221009A) is believed to be dominated by nonthermal synchrotron radiation throughout its duration (Yang et al 2023). So these bright GRBs clearly have different emission components.…”
Section: Comparison With Other Grbsmentioning
confidence: 63%
“…In the energy spectrum analysis, we found that there may be a photosphere emission component in the early phase of GRB 230307A, which is similar to that of the also very bright GRB 130427A (Preece et al 2014). However, the brightest of all time (the BOAT, GRB 221009A) is believed to be dominated by nonthermal synchrotron radiation throughout its duration (Yang et al 2023). So these bright GRBs clearly have different emission components.…”
Section: Comparison With Other Grbsmentioning
confidence: 63%
“…Then we perform spectral fitting by utilizing the Python package, MySpecFit, in accordance with the methodology outlined in Refs. 27,68 . The MySpecFit package facilitates Bayesian parameter estimation by wrapping the widely-used Fortran nested sampling implementation Multinest [69][70][71][72] .…”
Section: Spectral Analysismentioning
confidence: 99%
“…In addition, GRB 230307A poses higher total energy and harder spectra, likely indicating a more intense merger event. We also consider the scenario where the host galaxy has a redshift of 3.87 46 and notice that in this case, the isotropic energy of GRB 230307A is ∼ 10 56 erg, which is an order of magnitude larger than that of the brightest-of-all-time GRB 221009A 20,68 .…”
Section: Classificationmentioning
confidence: 99%
“…At 13:16:59.99 UT (T 0 ) on 2022 October 9, the Fermi Gamma-ray Burst Monitor triggered and located GRB 221009A (Veres et al 2022;Lesage et al 2023), which was also detected by the Fermi Large Area Telescope (Fermi-LAT; Bissaldi et al 2022), Konus-Wind (Frederiks et al 2022), Swift-BAT-GUANO (Dichiara et al 2022), GECAM-C (Liu et al 2022;An et al 2023;Yang et al 2023), and LHAASO (LHAASO Collaboration 2023). Its redshift is reported to be z = 0.151 (de Ugarte Postigo et al 2022).…”
Section: Fermi-lat Data Analysismentioning
confidence: 99%